Support to the Sierra Leone Land Agenda : Policy Note - Ahene, Rexford; Bagdonavicius, Arvydas; Barra, Alvaro Federico; Galpin, Claire (World Bank, Washington, DC, 2019)
Land administration in Sierra Leone is a complex issue. The current process of registration in Freetown is ineffective and disorganized, leading to a widening gap in the credibility of both the cadaster and registry. Surveying quality is inadequate due to lack of trained surveyors in modern electronic surveying and mapping techniques, and a shortage of equipment. Most of the confusion and contradictions dominating the typology of land issues in the provinces emanates from the general absence of well-established cadastral boundaries. The new national lands policy of Sierra Leone aspires to gradually formalize land transactions while respecting the customary systems. Mandatory land transaction recording and registration can be an effective step towards the implementation of land related policy. In parallel, communication and sensitization campaigns will be carried out to avoid situations where ignorance of the requirement to register land on a first served basis may violate the rights of genuine land owners because their land can be registered to somebody more familiar with the system. Government decentralization and empowerment of municipalities should improve the process efficiency. A Crucial requirement in order to build an effective and modern land administration and management system is to abandon the manual recording system and move towards a digital and computerized one.